Straits settlements Blue Book (imports/exports) 1919-1920 vol.71 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports during for the year 1919, 1920';'Statement of the quantities and value of imports and exports of the colony of the Straits Settlements from and to other Countries in 1918 and 1919, 1919 and 1920'.